Examine the Assessment Tools in Identifying and Sustaining a Company's Core-Competencies - Lim, Tze Hui (2011)
Organisations have learned that it is essential to continuously defining and re-defining their directions and goals over the past several decades. Also, the increased of globalized competition and rapid innovation have generated a new focus on enterprise-wide transformation (Rouse, 2005) with broader measurement of enterprise performance. Therefore, organisations often adopted the maturity model to assess the performance of their operations, and benchmark the best practices in order to enhance their processes.